Stability assessment of hygroscopic medications in one dose packaging using community pharmacist surveys and experimental storage methods - Takayuki Yoshida; Hisashi Iijima; Yumeka Washio; Makoto Toda; Miho Morikawa; Kazuhiro Iwasa; Takashi Tomita (Scientific Reports)
Abstract Some medications are unsuitable for one-dose packaging due to issues such as moisture absorption. A survey of community pharmacists was conducted to understand the status of one-dose packaging and identify hygroscopic medications for stability testing. Stability was assessed using a moisture-suppression bag and clinical applications were investigated. Survey results were used to extract the medications that should be included in the one-dose package. Medications were stored with and without moisture-suppression bags, and quality was assessed using weight change and breaking force. Suvorexant, Telmisartan, Aspirin Dialuminate, Kampo extract formulations (Yokukansan and Daikenchu-tou), and Yokuinin extract tablets were selected for the stability test. Storage without moisture-suppression bags resulted in substantial changes in weight and breaking force for all tested medications; the use of moisture-suppression bags maintained the quality of some medications. Although there was a substantial difference in weight change from day 3, there was almost no change in appearance. Currently, the decision to include hygroscopic pharmaceuticals in a single package based on changes in appearance is insufficient. However, further research is necessary to justify the decision not to include hygroscopic pharmaceuticals in such packaging. Therefore, pharmaceutical companies should cultivate appropriate awareness and information literacy of pharmacists should be improved.